HAIR GROWTH ACTIVITY AND SAFETY TEST OF ETHOSOMAL GEL ETHYL ACETATE FRACTION OF NOTHOPANAX LEAVES (NOTHOPANAX SCUTELLARIUM MERR.) - Jufri, Mahdi; Amelia, Lili; Munim, Abdul (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aims of this study were to know the hair growth activity from the ethosomal gel of ethyl acetate fraction compared to the nonethosomal gel of ethyl acetate fraction, as well as its ability to penetrate into the skin and its safety from ethosomal gel testing. Methods: The hair growth activity was measured by three parameters: Hair length, hair thickness, and hair weight. Results: The results obtained are shown that the ethosomal gel with concentration 1% has better hair growth activity rather than the ethosomal gel with concentration 0.5% and the nonethosomal gel but it has similarity to the positive control (minoxidil gel with concentration 2%). In vitro penetration test using Franz diffusion cells shown that the ethosomal gel with concentration 1% has cumulative penetration of quercetin higher than nonethosomal gel, which value was 3.3175Â±0.02 Î¼gcmâˆ’2 for the ethosomal gel with concentration 1%; and 2.7663Â±0.19 Î¼gcm-2 for the nonethosomal gel with flux values for the ethosomal gel with concentration 1% and the nonethosomal gel, respectively, are 0.4147Â±0.01 Î¼gcmâˆ’2hâˆ’1 and 0.3458Â±0.02 Î¼gcmâˆ’2hâˆ’1. Conclusion: As for the safety test using hen’s egg test-chorioallantoic membrane (HET- CAM) safety test) have shown that both concentrations 0.5% and 1% of the ethosomal gel can generate mild irritation for topical application.